MOTIVASI BERPRESTASI MAHASISWI KEPELATIHAN JURUSAN PENDIDIKAN OLAHRAGA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Fadillah Sari Ananda; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at the Campus Physical Education who is in Rumbai. The purpose of this study was to determine student achievement motivation in selecting a course of coaching. This study entitled "Coaching Programs Student Achievement Motivation Faculty of Physical Education Teaching and Education University of Riau" .Topic focus of this research is how the reasons and background of female students in selecting a course of coaching and how the student motivation to learn and practice in following the coaching education. In this study, the obtained will be analyzed quantitatively. Since this research is descriptive quantitative research, the technique analysis of the findings of the field (in the form of information resulting from filling the questionnaire or questionnaires, interviews, field notes documentation, etc.) in a way to describe and explain in detail the issues to be investigated based on obtained from research reports in the form of a questionnaire that has been collected, analyzed and spoken in sentences for harvest. By using census sampling method in which the sample as a whole and each member of the population has an equal chance. In this way the researchers will carry out the sampling gradually. As for the reasons and background of female students choose courses of coaching as constituted with the knowledge, experience, and interests. So with the knowledge that with their knowledge of coaching education student early to know, to know those sports, know the vision and mission of coaching and what ideals of education graduate student coaching. Experience is supported by the experience of student follow sports events and won the event. and interests are supported by their interest in the sport so that they can lead to achievement to student interest in the coaching education courses. Where with their knowledge, experience and interests that encourage female students to continue to improve motivation in learning and practicing, with their experience, knowledge and interests also encourage student motivation to continue to excel in sports. Keywords: Motivation, Achievement, Coaching Courses